Combined anti CXC receptors 1 and 2 therapy is a promising anti-inflammatory treatment for respiratory diseases by reducing neutrophil migration and activation. (October 2015) - Planagumà, A.; Domènech, T.; Pont, M.; Calama, E.; García-González, V.; López, R.; Aulí, M.; López, M.; Fonquerna, S.; Ramos, I.; de Alba, J.; Nueda, A.; et al.
Abstract: Neutrophil infiltration and activation in the lung are important pathophysiological features in COPD, severe asthma and bronchiectasis mostly mediated by CXCL8 and CXCL1 via CXCR1 and CXCR2. No thorough study to date has been performed to compare the anti-inflammatory effect profile of dual CXCR1/2 vs. selective CXCR2 antagonists in relevant human neutrophil assays and pulmonary inflammation models. Dual CXCR1/2 (SCH527123, diaminocyclobutandione-1) and selective CXCR2 (SB265610, thiopyrimidine-1) antagonist activity and receptor residence time were determined by [ 35 S]GTPγS binding in human ( h )- and guinea pig ( gp )-CXCR1 and CXCR2 overexpressing membranes. h -neutrophil chemotaxis, degranulation and ROS production were established using CXCL8 or CXCL1 to evaluate dual CXCR1/2- or selective CXCR2-dependent activities. LPS-induced lung inflammation in gp was selected to assess in vivo potency. Dual CXCR1/2 antagonists blocked both CXCL8 and CXCL1-induced h -neutrophil functions and [ 35 S]GTPγS binding. In contrary, selective CXCR2 antagonists displayed significantly reduced potency in CXCL8 -mediated h -neutrophil responses despite being active in CXCR2 assays. Upon LPS challenge in gp, administration of SCH527123 inhibited the increase of neutrophils in BALF, modestly reduced blood neutrophils and induced minor neutrophil accumulation in bone marrow. Differentiation of CXCR1/2 vs. CXCR2 antagonists could not be extended to in vivo due to differences in CXCR1 receptor homology between h and gp . Dual CXCR1/2 therapy may represent a promising anti-inflammatory treatment for respiratory diseases reducing more effectively neutrophil migration and activation in the lung than a CXCR2 selective treatment. However, the in vivo confirmation of this claim is still missing due to species differences in CXCR1.